1982
DOI: 10.1577/1548-8659(1982)111<624:eodocs>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dewatering on Chinook Salmon Redds: Tolerance of Four Developmental Phases to Daily Dewaterings

Abstract: Four intergravel developmental phases of chinook salmon Oncorhynchus tshawytscha were dewatered experimentally in artificial redds. The redds consisted of aquaria containing a gravel mix and supplied with 4 liters of water per minute at 10 C. Cleavage eggs and embryos (the egg phases), and eleutheroembryos and pre‐emergent alevins (the alevin phases) were dewatered 20 consecutive times in 22‐day tests. The egg phases were considerably more tolerant than the alevins. Some cleavage eggs were killed by 12‐ and 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 1 publication
1
51
0
Order By: Relevance
“…Stranding can be classified into two categories: beach stranding, when fish flounder out of the water on the substrate; and entrapment, when fish are isolated in pockets of water (e.g., in potholes) with no access to the free-flowing surface water (Higgins and Bradford 1996;Hoffarth 2004;Hunter 1992). Stranding has been observed in several field studies (e.g., Bauersfeld 1978;Hamilton and Buell 1976;Olson and Metzgar 1987) and can result in desiccation, temperature stress, hypoxia, predation, and mortality of fish eggs, fry, juvenile, and sometimes adult fish (e.g., Becker et al 1982;Hoffarth 2004;Hunter 1992) with consequent impacts on fish populations. Becker et al (1982) observed that eggs and fry were most vulnerable to high temperature stress when temperature rose to 20-25°C from an ambient river temperature of 6°C.…”
Section: Strandingmentioning
confidence: 98%
See 1 more Smart Citation
“…Stranding can be classified into two categories: beach stranding, when fish flounder out of the water on the substrate; and entrapment, when fish are isolated in pockets of water (e.g., in potholes) with no access to the free-flowing surface water (Higgins and Bradford 1996;Hoffarth 2004;Hunter 1992). Stranding has been observed in several field studies (e.g., Bauersfeld 1978;Hamilton and Buell 1976;Olson and Metzgar 1987) and can result in desiccation, temperature stress, hypoxia, predation, and mortality of fish eggs, fry, juvenile, and sometimes adult fish (e.g., Becker et al 1982;Hoffarth 2004;Hunter 1992) with consequent impacts on fish populations. Becker et al (1982) observed that eggs and fry were most vulnerable to high temperature stress when temperature rose to 20-25°C from an ambient river temperature of 6°C.…”
Section: Strandingmentioning
confidence: 98%
“…Stranding has been observed in several field studies (e.g., Bauersfeld 1978;Hamilton and Buell 1976;Olson and Metzgar 1987) and can result in desiccation, temperature stress, hypoxia, predation, and mortality of fish eggs, fry, juvenile, and sometimes adult fish (e.g., Becker et al 1982;Hoffarth 2004;Hunter 1992) with consequent impacts on fish populations. Becker et al (1982) observed that eggs and fry were most vulnerable to high temperature stress when temperature rose to 20-25°C from an ambient river temperature of 6°C. Although some eggs can survive stranding if kept moist at appropriate temperatures, alevins are more vulnerable because they cannot Fig.…”
Section: Strandingmentioning
confidence: 98%
“…The extent and duration of flow alteration and the stage of 40 development will influence the survival, and newly hatched alevins are less tolerant ; 41 . If not subjected to extreme temperatures (in this case warm water) or predation, 42 laboratory studies have confirmed that salmonid eggs may survive for weeks in dewatered gravel if they are kept 43 moisty (Becker et al, 1982;Reiser & White, 1983). The aim of our study was to 44 investigate the survival of Atlantic salmon eggs in a large area of potential spawning grounds that is permanently 45 dewatered during most of the egg incubation period due to regulation.…”
Section: Introductionmentioning
confidence: 99%
“…W ater temperature was monitored with a data logger (Onset Computer Corp., Pocasset, MA) to allow for an accurate calculation of accumulated temperature units (ATUs), a standard descriptor for early developmental stages in fish. One temperature unit equals the number of degrees Celsius (above freezing) for a period of 24 hours (Becker et al 1982).…”
Section: Freshwater Husbandrymentioning
confidence: 99%
“…This is a modification of a standard hatchery practice used to identify and remove unfertilized eggs (e.g., Leitritz and Lewis 1980 Alevins were transferred ('ponded') to rearing tanks January 29-30, 1998 (892-911 ATUs). Ponding time was determined based on elapsed ATUs (Becker et al 1982) and the physical appearance of the alevins (degree of yolk sac absorption). Ponding is timed to coincide with the commencement of exogenous feeding.…”
Section: Freshwater Husbandrymentioning
confidence: 99%